2022
DOI: 10.1530/joe-21-0242
|View full text |Cite
|
Sign up to set email alerts
|

Exercise does not improve insulin resistance and mitochondrial characteristics together

Abstract: The aim of this study was to investigate the relationship between mitochondrial content and respiratory function and whole-body insulin resistance in high fat diet (HFD) fed rats. Male Wistar rats were given either a chow diet or a HFD for 12 weeks. After four weeks of the dietary intervention, half of the rats in each group began eight weeks of interval training. In vivo glucose and insulin tolerance were assessed. Mitochondrial respiratory function was assessed in permeabilised soleus and white gastrocne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In terms of improving systemic glucose metabolism, consistent with previous studies, we found that gAd significantly reduced blood glucose levels and improved impaired glucose tolerance in high-fat diet mice, which is in agreement with the improvement of glucose metabolism by aerobic exercise. 37 , 38 Additionally, muscle lipid deposition is considered to be an important determinant of insulin resistance in skeletal muscle, 39 , 40 since increases in intramyocellular lipid and intermyocellular adipose tissue are associated with impaired skeletal muscle insulin signaling. Our study found that either exercise or gAd intervention reduced lipid ectopic deposition in the quadriceps muscle of mice and that SESN2 was involved.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of improving systemic glucose metabolism, consistent with previous studies, we found that gAd significantly reduced blood glucose levels and improved impaired glucose tolerance in high-fat diet mice, which is in agreement with the improvement of glucose metabolism by aerobic exercise. 37 , 38 Additionally, muscle lipid deposition is considered to be an important determinant of insulin resistance in skeletal muscle, 39 , 40 since increases in intramyocellular lipid and intermyocellular adipose tissue are associated with impaired skeletal muscle insulin signaling. Our study found that either exercise or gAd intervention reduced lipid ectopic deposition in the quadriceps muscle of mice and that SESN2 was involved.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial content and morphology are responsive to both diet-induced obesity and exercise in mouse and human skeletal muscle [ [44] , [45] , [46] , [47] ], potentially via mitochondrial oxidants [ 48 , 49 ]. Our previous research established a link between increased NOX2 activity and the mitochondrial complex I subunit NDUFB8 expression in mouse skeletal muscle followed by a HIIT intervention [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the literature agrees that exercise training interventions supported by adequate parameters of intensity and frequency are associated with several health benefits [ 1 ]. Evidence shows that early introduction of ET can revert some metabolic disorders, such as hypercholesterolemia, insulin resistance, and fat deposition not only in humans [ 2 , 3 ] but also in experimental models [ 4 , 5 ]. Moreover, exercise training effects are mediated by adaptive changes not only in skeletal muscles but also in multiple body tissues, including the heart, adipose tissue, nervous system, and liver [ 1 ].…”
Section: Introductionmentioning
confidence: 99%